1995
DOI: 10.1139/f95-057
|View full text |Cite|
|
Sign up to set email alerts
|

Stock-recruitment models for Pacific sardine (Sardinops sagax)

Abstract: We used generalized additive models to study the recruitment of Pacific sardine (Sardinops sagax) along western North America and to compare the effects of fishing and environmental factors on the stock. We found significant relationships between the logarithm of sardine reproductive success (recruits per unit of spawning biomass) and average sea surface temperature (SST), as well as between sardine recruitment, spawning biomass, and average SST. Simulation and time series analyses were used to evaluate bias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
154
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 19 publications
7
154
0
2
Order By: Relevance
“…Time series of recruitment at age 3 from 1908 to 1998 were taken from Toresen & Østvedt (2000) and the temperature recorded at the Kola section were averaged over the months January to April, from 1905to 1995(Tereshchenko 1996 (Fig. 3).…”
Section: Atlanto-scandian Herringmentioning
confidence: 99%
“…Time series of recruitment at age 3 from 1908 to 1998 were taken from Toresen & Østvedt (2000) and the temperature recorded at the Kola section were averaged over the months January to April, from 1905to 1995(Tereshchenko 1996 (Fig. 3).…”
Section: Atlanto-scandian Herringmentioning
confidence: 99%
“…While environmental variability has been recognized as exerting a substantial influence on the recruitment and productivity of fish stocks (Vert-pre et al, 2013;Szuwalski et al, 2014), this information has not been widely incorporated into fish population models and projections. However, recent examples have demonstrated that population projections used to set catch quotas and rebuilding plans can be more reliable for some stocks if environmental factors, particularly temperature, are considered in projections (Jacobson and McClatchie, 2013;Hill et al, 2014;Pershing et al, 2015;Tommasi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Year-to-year variability in temperature has been shown to be linked to changes in fish year-class strength for a number of species (Mysak et al 1982, Murray et al 1983, Swartzman et al 1983, Hansen & Buch 1986, Jacobson & MacCall 1995. Atlantic cod Gadus morhua is widely distributed in the waters of the North Atlantic and surrounding seas and occurs in water temperatures in the range -1 to 12°C.…”
Section: Introductionmentioning
confidence: 99%